Community Perceptions About Online Buying Business Through Facebook Social Media - Wulandari; Yenrizal; Badarudin Azarkasyi (CV. Era Digital Nusantara, 2024)
The purpose of this study is to find out how the perception and development of people who do online buying and selling business through social media Facebook. This research method uses qualitative research methods or case studies. This study uses data collection techniques such as interviews, documentation and questionnaires as complementary data. The theory used is the theory of symbolic interactionism. The results of this study indicate that people who do online buying and selling businesses are motivated by opportunities and opportunities to take advantage of their technological and communication advances, then the communication they build through social media Facebook in doing online buying and selling business is very effective and acceptable to the community. As well as the development of creative and innovative communities when doing online buying and selling businesses are able to help people develop their ideas and hobbies, even though they are quite far from the city, this can be seen from people who do online buying and selling businesses are able to understand and use social media Facebook as a business buying and selling online well.